Point of Care testing: The future of periodontal dis-ease diagnosis and monitoring - Mohamad Khorshid (College of Dentistry/ University of Baghdad, 2022)
Manual probing and periodontal charting are the gold standard for periodontal diagnosis that have been used in practice over a century. These methods are affordable and reliable but they are associated with some drawbacks that cannot be avoided. Among these issues is their reliance on operator's skills, time-consuming and tedious procedure, lack sensitivity especially in cases of early bone loss, and causing discomfort to the patient. Availability of a wide range of biomarkers in the oral biofluids, dental biofilm, and tissues that potentially reflect the periodontal health and disease accurately encouraged their use as predictive/diagnostic/monitoring tools. Analysing biomarkers during care-giving to the patient using chairside kits is known as Point of Care (POC) testing. Introduction of POC in periodontal practice could provide more flexibility and add further dimensions to the process of diagnosis and tailoring more precise treatment plan for the patients. This review aimed to highlight available POC testing used for periodontal diagnosis and disease prediction/monitoring